PERANCANGAN HOTEL BUTIK THE HOUSE TOUR BANDUNG DENGAN PENDEKATAN GAYA DESAIN INTERIOR POP ART - Stela Amabel; Jamaludin Jamaludin (Universitas Mercu Buana, 2023)
This paper explores the fusion of Pop Art and the hospitality business in the context of designing a boutique hotel with a vibrant and energetic atmosphere. Pop Art, a revolutionary artistic movement of the 20th century, with its bold colors, dynamic patterns and iconic imagery, has made a strong impact on various domains, including interior design. The aim of this paper is to design a boutique hotel by integrating Pop Art principles to provide a new experience to hotel guests. This article explores key elements of Pop Art, such as vibrant color palettes, graphic patterns, and iconic references, and illustrates how these elements can be blended in balance into a boutique hotel interior space. This design model paper discusses the importance of creating a cohesive visual narrative that pays homage to the Pop Art movement while maintaining a sophisticated and contemporary feel. The method used is design exploration and experimentation, namely trying to integrate Pop Art into hotel spaces and the potential challenges and considerations when implementing Pop Art designs in a hospitality environment, including balance, functionality, and comfort. Through exploring the case study of The House Tour Bandung, this paper hopes to provide inspiration and guidance for designers, hoteliers, and art enthusiasts interested in creating a truly unique and immersive Pop Art-inspired boutique hotel.